AN OBSERVATIONAL STUDY TO EVALUATE KNOWLEDGE, ATTITUDE, AND PRACTICE OF PHARMACOVIGILANCE AMONG THE HEALTHCARE PROFESSIONALS AND UNDERGRADUATE MEDICAL STUDENTS - PATEL, JAYDEEP; CHAUDHARI, VIPUL; THAKER, VIDHI (International Journal of Current Pharmaceutical Research, 2026)
Objective: The importance of pharmacovigilance (Pv) is to ensure the safe and rational use of medicines. Targeting healthcare professionals (HCPs) and undergraduate (UG) medical students (visiting hospitals) for sensitization towards pharmacovigilance is the key to implementing the practice of adverse drug reaction (ADR) reporting in clinical practice. Education and training are the most recognized means of improving ADR reporting. The objective was to evaluate the knowledge, attitude, and practices (KAP) of pharmacovigilance among HCPs and UG medical students. Methods: This was a cross-sectional, observational, questionnaire-based study carried out for a period of four months (September to December 2023). The case record form includes demographic characteristics and a KAP questionnaire that focuses on the reporting of adverse drug reactions (ADRs). A KAP survey was analyzed question-wise, and statistical analysis was performed using Microsoft Excel Office 365. Results: The results indicated that HCPs demonstrated a higher level of knowledge (78.14%) compared to UG medical students (70.2%). Both groups demonstrated an equally positive attitude towards pharmacovigilance, with a mean score of 93%. However, a significant difference was observed in the practice domain, where HCPs scored 70.9%, which was markedly higher than the 41.68% recorded among UG medical students. Conclusion: The study reveals that more sensitization programs on pharmacovigilance practice are required in tertiary care hospitals to ensure ADR reporting to the pharmacovigilance centre, which will strengthen the health care setup.